2011
DOI: 10.1089/ten.tea.2010.0463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Retinoic Acid on Keratinocyte Proliferation and Differentiation in a Psoriatic Skin Model

Abstract: Psoriasis is a skin disease characterized by the presence of red plaques on the skin. This pathology is well-known to be a retinoid-sensitive disease. Previous investigations have shown that retinoids can modulate epidermal proliferation with an antiproliferative potential in hyperproliferative skins. The aim of this study was to compare the development of psoriatic substitutes cultured in a retinoic acid supplemented medium with those cultured in medium receiving no supplement, to define the effects of this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…Vitamin A is of particular interest in psoriasis management due to its regulatory role in keratinocyte proliferation and differentiation . Certain carotenoids found in fruits and vegetables – namely α‐carotene, β‐carotene and β‐cryptoxanthin – are converted to vitamin A endogenously and thus also are of interest in relation to psoriasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A is of particular interest in psoriasis management due to its regulatory role in keratinocyte proliferation and differentiation . Certain carotenoids found in fruits and vegetables – namely α‐carotene, β‐carotene and β‐cryptoxanthin – are converted to vitamin A endogenously and thus also are of interest in relation to psoriasis .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A is of particular interest in psoriasis management due to its regulatory role in keratinocyte proliferation and differentiation. [13][14][15] Certain carotenoids found in fruits and vegetables namely a-carotene, b-carotene and b-cryptoxanthinare converted to vitamin A endogenously and thus also are of interest in relation to psoriasis. [16][17][18] Some studies found lowered levels of carotenoids and vitamin A in the serum and skin of psoriasis patients, and the authors hypothesized that deficiencies in these micronutrients contributed to the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study [Jean et al, 2011] performed by the same group, the authors confirmed their conclusion regarding the importance of epidermal keratinocytes for the development of the diseased skin phenotype. There they compared how the same sets of samples reacted to the presence of all-trans-retinoic acid (ATRA) in the cell culture medium.…”
Section: Clarification Of the Crosstalk Of Keratinocytes And Fibroblamentioning
confidence: 58%
“…In general, retinoids promote proliferation in normal human skin, whereas they lead to a reversal of hyperproliferation in lesional psoriatic epidermis. In this context, we note that the concentration of ATRA used by Jean et al [2011] significantly exceeded the physiological level (10 -8 -10 -9 M ). Thus, it caused shrinkage of their ATRA-treated samples far beyond the control values.…”
Section: Clarification Of the Crosstalk Of Keratinocytes And Fibroblamentioning
confidence: 77%
“…In 2011, they demonstrated for the first time that pathological substitutes produced by the self-assembly approach can be treated with an anti-psoriatic molecule and react positively to the treatment such as observed in psoriatic skin in vivo. This functional study suggests that the self-assembled skin substitutes could be useful to better understand the mechanisms through which retinoic acid regulates cellular physiology in psoriatic skin, and could become an effective and innovative dermopharmaceutical tool for the screening of new treatments (Jean et al, 2011).…”
Section: Self-assembly Approachmentioning
confidence: 90%